Hans-Georg Gadamers Sprachlichkeit der hermeneutischen Erfahrung im Wechselspiel von Vernunft und Erfahrung, Wissenschaft und/oder soziale Vorstellungen, Tradition(en) und/oder Gemeinschaft am Beispiel von Thomas Morus’ Utopia - Arnswald, Ulrich (Labyrinth, 2022)
Hermeneutics can be understood on the one hand as the art of interpretation, and on the other hand as a medium for dealing with the past, for conveying events, contexts or even writings in new ways of speaking for new recipients. The interpretation of writings, however, places special demands on hermeneutics: it does not take place in a sterile vacuum, but is rather embedded in a social and cultural context that shapes the interpretation or mediation and is an expression of a time, a fashion or a specific requirement of modernity. The question therefore arises as to what role reason and experience, science and/or social ideas, tradition(s) and/or community play in interpretation. Using Thomas More's masterpiece Utopia as an example, various resulting interpretative approaches to a concrete writing will be presented. Through the hermeneutic design of a historical horizon in relation to Thomas More's time as well as through the development of a historical awareness of the work, the possibility of an understanding of this world-famous, still controversial writing as well as the efficiency of Gadamer's philosophical hermeneutics will become recognisable.